Preparation and Characterization of Cu(II)- and Pt(II)-Thiourea Complexes and Adsorption of Pt(II) Complex on Local Bentonite - Sulaiman, Ahmed Mohammed; Awwad, Abdulaziz Khaled (Indonesian Journal of Chemistry, 2025)
This study investigates the stability and adsorption behavior of inorganic complexes formed from the reaction of 2-aminopyridine with phenyl isothiocyanate to produce thiourea derivatives, which were further reacted with copper salts and platinum phosphine. The complexes were characterized using UV-vis and FTIR spectroscopies, revealing a 2:1 (ligand-to-metal) ratio and high stability. The effect of temperature on the stability showed a slight increase in absorption values with rising temperature. Stability constants and thermodynamic functions confirmed the complexes' stability at room temperature. Additionally, the adsorption of the platinum complex (AL2) onto bentonite clay was studied. Before and after adsorption, the bentonite surface was analyzed using UV-vis, FTIR, AFM, and SEM techniques. Adsorption isotherms followed Freundlich model, and adsorption kinetics followed first-order reaction model. The study aims to prepare and characterize copper-thiourea and platinum-phosphine complexes, calculate their stability constants, and explore the adsorption behavior of AL2 on bentonite. The results highlight the high stability of the complexes and the successful modeling of AL2 adsorption, suggesting their potential applications in catalysis and environmental remediation.